Hirudo verbana Microbiota Dynamics: A Key Factor in Hirudotherapy-Related Infections? - Djursun Karasartova; Gonul Arslan-Akveran; Sabiha Sensoz; Kosta Y. Mumcuoglu; Aysegul Taylan-Ozkan (Microorganisms)
The gastrointestinal microbiota of medicinal leeches is particularly interesting due to their blood-feeding habits, increasing medical use, and risk of pathogen transmission. Three groups of Hirudo verbana were used to study the leech microbiota: farmed leeches fasting for a long time, farmed leeches recently fed with bovine blood, and wild specimens fed with amphibian blood. The microbiota of the leeches’ mouth, pharynx, crop, and intestine was analyzed. Metasequencing analyses were performed using amplification of the 16S rRNA V3-V4 region on a NovaSeq Illumina platform. The relative abundance of bacterial microbiota included environmental bacteria from the families Rhizobiaceae, Comamonadaceae, Sphingobacteriaceae, Phreatobacteraceae, Myxococcaceae, Chitinophagaceae, Rhodospirillaceae, and Bdellovibrionaceae, as well as symbiotic/probiotic bacteria such as Mucinivorans, Aeromonas, Vagococcus, Lactobacillales, and Morganella. Significant differences were found in the different regions of the digestive system among the three groups of leeches, and environmental bacteria were present in all groups to varying degrees. A negative correlation was found between the dominant environmental and the symbiotic/probiotic bacteria. In contrast, a positive correlation was found between environmental and symbiotic/probiotic bacteria, indicating their association with host factors. Microbiota diversity, abundance, and bacterial correlations may be influenced by factors such as the leech’s fasting state, blood meal source, and environmental conditions. The identified opportunistic pathogens, such as Rickettsia, Anaplasma, and Treponema, identified for the first time in H. verbana, should be taken into consideration when using this leech in hirudotherapy. Our results show that extensive screening for opportunistic and pathogenic agents should be performed on leeches intended for medical use. Long-fasting leeches and leeches cultured in specialized farms are recommended for hirudotherapy.